2013
DOI: 10.1097/dbp.0b013e31827a3a22
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Vanderbilt Attention-Deficit Hyperactivity Disorder Diagnostic Parent Rating Scale in a Community Population

Abstract: The confirmation of the construct and concurrent criterion validities found in this study further support the utility of the VADPRS as a diagnostic rating scale for ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 30 publications
(12 reference statements)
4
70
0
4
Order By: Relevance
“…It was demonstrated that SWAN can reliably differentiate ADHD from non-ADHD psychiatric controls. Moreover, the SE and SP found in the current study (SE 76%–96%, SP 68%–95%) were generally similar or better than the other rating scales for ADHD, including ADHD Rating Scale (SE 63%–84%, SP 49%–86%), Connors’ Rating Scale (SE 78%–92%, SP 91%–94%),30 Vanderbilt Rating Scale (SE 67%–80%, SP 75%–86%),31 and the previous local study (SE 55%–83%, SP 66%–89%) and international studies on SWAN (SE 86%, SP 88%) 19,20…”
Section: Discussionsupporting
confidence: 70%
“…It was demonstrated that SWAN can reliably differentiate ADHD from non-ADHD psychiatric controls. Moreover, the SE and SP found in the current study (SE 76%–96%, SP 68%–95%) were generally similar or better than the other rating scales for ADHD, including ADHD Rating Scale (SE 63%–84%, SP 49%–86%), Connors’ Rating Scale (SE 78%–92%, SP 91%–94%),30 Vanderbilt Rating Scale (SE 67%–80%, SP 75%–86%),31 and the previous local study (SE 55%–83%, SP 66%–89%) and international studies on SWAN (SE 86%, SP 88%) 19,20…”
Section: Discussionsupporting
confidence: 70%
“…First, although the Vanderbilt Scales are widely used and have demonstrated acceptable psychometric properties for the symptom scales, 33 the psychometric strength of the impairment items has not yet been established. Future investigations of symptom-impairment correspondence would likely be strengthened by using multiple items from well-validated measures of functional impairment to capture a more comprehensive picture of the impact of symptom improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The VADPRS was developed to directly correspond to the 18 core symptoms of ADHD that are specified in the DSM-IV [14]. The scale has strong internal consistency and corresponds well to a more in-depth diagnostic interview for ADHD [14, 15]. However, convergent validity with direct child assessments (such as continuous performance tests) has not been explored for the VADPRS.…”
Section: Introductionmentioning
confidence: 99%